2010
DOI: 10.1111/j.1365-246x.2010.04742.x
|View full text |Cite
|
Sign up to set email alerts
|

Reducing local hydrology from high-precision gravity measurements: a lysimeter-based approach

Abstract: S U M M A R YTemporal gravimeter observations, used in geodesy and geophysics to study the Earth's gravity field variations, are influenced by local water storage changes (WSC). At the Geodetic Observatory Wettzell (Germany), WSC in the snow pack, top soil, unsaturated saprolite and fractured aquifer are all important terms of the local water budget. In this study, lysimeter measurements are used for the first time to estimate the hydrological influence on temporal gravimeter observations. Lysimeter data are u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 61 publications
0
46
0
Order By: Relevance
“…(17) and (20)), is not consistent with that observed, in terms of both the increased gravity amounts during precipitation and the rates of gravity decrease after precipitation. A potential cause of this inconsistency is the horizontal heterogeneity of the water distribution in the vicinity of the gravimeter; for the case of Mizusawa, the gravity observation building itself could affect the horizontal water heterogeneity, and the subsequent gravity disturbance (e.g., Creutzfeldt et al, 2010a). Thus, in the following subsection, an effect of the building will also be taken into account when estimating the water distribution and the gravity change.…”
Section: Modeled Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(17) and (20)), is not consistent with that observed, in terms of both the increased gravity amounts during precipitation and the rates of gravity decrease after precipitation. A potential cause of this inconsistency is the horizontal heterogeneity of the water distribution in the vicinity of the gravimeter; for the case of Mizusawa, the gravity observation building itself could affect the horizontal water heterogeneity, and the subsequent gravity disturbance (e.g., Creutzfeldt et al, 2010a). Thus, in the following subsection, an effect of the building will also be taken into account when estimating the water distribution and the gravity change.…”
Section: Modeled Resultsmentioning
confidence: 99%
“…Wziontek et al (2009) explained a seasonal gravity change of ∼10 µgal peak-to-peak at superconducting gravity stations in Europe by attraction and loading effects attributable to global land-water distributions. Creutzfeldt et al (2010a, b) reproduced a non-tidal gravity change of ∼10 µgal in amplitude at Wettzell, Germany, by using spatial integrations of local water distributions observed with a lysimeter and borehole moisture meters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These residuals are considered to be caused by hydrological mass variations because all other possible effects on temporal gravimeter measurements are assumed to be negligible for Wettzell (e.g., postglacial rebound or processes in the Earth's mantle and core). For the SG Wettzell, Creutzfeldt et al (2008) showed that between 52% and 80% of the local hydrological gravity signal is generated within a radius of 50 m around the SG, and 90% of the signal comes from an area within a radius of around 1000 m. A high correlation of independently estimated WSC in this area and SG residuals (coefficient of determination: 0.97; corresponding slope: 1.06) proved that a major part of the gravity residuals is generated by WSC in this area (Creutzfeldt et al, 2010b). In the present study, the large-scale hydrological effect on gravimeters (e.g., Llubes et al, 2004;Weise et al, 2009) the dominant local hydrological influence and high uncertainties in the modelling of large-scale WSC (e.g., Werth et al, 2009b).…”
Section: Gravity Datamentioning
confidence: 82%
“…This might be due to the fact that GPS is sensitive to changes in largescale phenomena related to mismodelling of EOPs, orbits, satellite antenna PCV or hydrodynamics as large scale atmospheric or hydrological effects (Dong et al 2006), while SG is extremely sensitive to local influences, mostly due to the changes in the continental water storage (e.g. Longuevergne et al 2009;Naujoks et al 2010or Creutzfeldt et al 2010. As it was previously emphasized hydrology-induced gravity variation is the only factor limiting the observations from SGs to be used for geodynamical purposes (Mikolaj et al 2015) as the contribution of hydrosphere is station-dependent (Wziontek et al 2009).…”
Section: Stochastic Partmentioning
confidence: 99%